Lubrication of poly(vinyl alcohol) chain orientation by carbon nano‐chips in composite tapes. Issue 4 (17th May 2012) - Song, Kenan; Zhang, Yiying; Meng, Jiangsha; Minus, Marilyn L.
Abstract: The extraordinary structural properties of graphene and carbon nanotube materials motivate the development of practical methods for their use in fabricating continuous, strong, and tough composite fibers. Poly(vinyl alcohol) (PVA)/carbon nano‐chip fiber (CNCF) composite tapes with 0.5 wt % loading show that Young's modulus, tensile strength, and toughness are increased by 585%, 653%, and 20%, respectively as compared to the control (PVA) tapes. Nano‐chips exfoliated from the CNCF during processing, lubricate polymer chain alignment, and orientation during drawing, where composite tapes could be drawn to higher draw ratios compared with the control tapes. As a result, the Herman's orientation factor ( f ) increased from 0.5 (control tape) to 0.8 (composite tape). Theoretical analysis shows ∼ 16 vol % of the composite tapes consists of fully oriented PVA chains, which contributes to its exceptional mechanical performance. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :